Formulasi Granul Effervescent Ekstrak Etanol Buah Andaliman (Zanthoxylum acanthopodium DC.) Dengan Variasi Sumber Asam dan Uji Aktivitas Antioksidan - Yunahara Farida; Kartiningsih Kartiningsih; Febria Hana Rahmadani (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Andaliman fruit (Zanthoxylum acanthopodium DC.) contain flavonoids that has antioxidantactivity. This study was conducted to obtain the effervescent granules andaliman fruit extract which has the highest antioxidant activity by DPPH free radical scavenging method. Andaliman fruit was extracted in stages using n-hexane, ethyl acetate and 70% ethanol, then dried using freeze drying method. Furthermore, the dry extract of ethanol is formulated using variation acid sources, namely citric acid and tartaric acid. The results showed that the formulas had moisture rate of 2.30 – 3.95%; fl ow rate of 2.53-4.12 g/sec; the particle size distribution with the fi nes <10%; dissolved time < 2 minutes; and a pH value of 5.48-5.65. The results of the antioxidant activity of formula I-III were 74.0; 84.9 and 91.9 ppm respectively. The conclusion of the research showed that the formula I with a combination of citric acid and tartaric acid is a formula that meets the physical quality requirements and has a strong antioxidant activity with IC50 value of 74.0 ppm.